2017
DOI: 10.1108/hff-03-2016-0134
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of flow structures in a turbulent separating flow using hybrid RANS-LES model

Abstract: Purpose Hybrid Reynolds-averaged Navier–Stokes large eddy simulation (RANS-LES) methods have become popular for simulation of massively separated flows at high Reynolds numbers due to their reduced computational cost and good accuracy. The current study aims to examine the performance of LES and hybrid RANS-LES model for a given grid resolution. Design/methodology/approach For better assessment and contrast of model performance, both mean and instantaneous flow fields have been investigated. For studying ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…The airflow around the model can be regarded as the 3D incompressible viscous isothermal flow. In consideration of its accuracy in studies (Ahoward and Pourquie, 2002;Kumar et al, 2017;Garcia et al, 2017), the LES model is introduced. Filtered Navier-Stokes' equations are shown as follows:…”
Section: Governing Equations and Discretizationmentioning
confidence: 99%
“…The airflow around the model can be regarded as the 3D incompressible viscous isothermal flow. In consideration of its accuracy in studies (Ahoward and Pourquie, 2002;Kumar et al, 2017;Garcia et al, 2017), the LES model is introduced. Filtered Navier-Stokes' equations are shown as follows:…”
Section: Governing Equations and Discretizationmentioning
confidence: 99%
“…( 14). This non-linear correction to SST model is adopted from Abe et al [22] and more details on the exact expression used in this study can be found in Kumar et al [23,24].…”
Section: Non-linear Shear Stress Transport Model (Nsst)mentioning
confidence: 99%
“…where ' ̅ 'denotes averaging over time. Further details regarding the computation of POD modes and reconstruction can be found in the published literature [18][19][20][21][22] .…”
Section: B Proper Orthogonal Decompositionmentioning
confidence: 99%